Motor features of abstract verbs determine their representations in the motor system - Li, Xiang; Luo, Dan; Wang, Chao; Xia, Yaoyuan; Jin, Hua (Frontiers in Psychology, 2022)
Embodied cognition theory posits that concept representations inherently rely on sensorimotor experiences that accompany their acquisitions. This is well established through concrete concepts. However, it is debatable whether representations of abstract concepts are based on sensorimotor representations. This study investigated the causal role of associated motor experiences that accompany concept acquisition in the involvement of the motor system in the abstract verb processing. Through two experiments, we examined the Action-sentence Compatibility Effect, in the test phase after an increase in motor features during the learning phase for abstract verbs with low motor features (Experiment 1) or novel words with no conceptual features at all (Experiment 2). After associated motor experiences were added in the word learning phase, Action-sentence Compatibility Effect was found in the semantic processing tasks during the test phase for abstract verbs (Experiment 1a) and novel words (Experiment 2). This was lacking in the word font color judgement task requiring no semantic processing (Experiment 1b). Coupled with our previous study, these findings suggest that motor features formed during word learning could causally affect embodiment in the motor system for abstract verbs, and reactivation of motor experiences in abstract verb processing depends on a given task’s demands. Our study supports the view that conceptual representations, even abstract concepts, can be grounded in sensorimotor experiences.